Diagnóstico del sistema de transporte público colectivo de cajicá (2020)
For this work, a field study was carried out in the municipality of Cajicá, where the number of passengers getting on and off inter-municipal vehicles was determined. This in order to determine the travel times, the supply and the demand of the users.